HESITANCY TOWARDS ONLINE SHOPPING, A STUDY OF PAKISTANI CONSUMERS - Usman YOUSAF; Mohsin ALTAF; Noman SARWAR; Syed Ali Hassan SHAH (Management & Marketing)
To study the influence of Perceived cost, risk, convenience and enjoyment on online consumer purchases. Being more convenient online shopping seems painless compared to in store shopping, why consumers are still reluctant to shop online?.A sample of 220 questionnaires was filled from different departments at University of Sargodha. Respondents were asked to fill the questionnaire based on four factors (Perceived cost, Perceived risk, Perceived convenience, Perceived enjoyment), there were 2 general questions. Out of 220, 207 questionnaires were returned. One sample test is applied in this study to check the reliability of independent variables. Analysis was also done on basis of gender and their ages. The most important factor out of four, which can persuade the customer's online buying decision, is delivery cost for purchased items and it has negative relationship with dependent variable, moreover perceived risk has also negative relationship with dependent one. Perceived convenience and Perceived enjoyment has positive relationship with online shopping preference. As online shopping is easier to do but due to extra delivery cost and risk factors consumers do not adopt online shopping and these factors should be minimized to promote online shopping. Online shopping should be promoted and to gain the consumer confidence, delivery cost and risk factor should be minimized. As online shopping is easier to do as compared to offline shopping but people still reluctant to use internet for online shopping, so to promote online shopping delivery cost and risk factor should be minimized to gain consumers attraction and confidence. People want to experience online shopping but it won’t be promoted until delivery cost and perceived risk factors be reduced. A little work has been done on exploring the factors that influence the online buying decision. These factors are called situational factors and include delivery charges, risk factors, convenience factors and enjoyment factors. In Pakistan consumers are not too much affiliated to online shopping as compared to European countries and not too much researches have been done related to online shopping in Pakistan , so this research been conducted to promote online shopping.